The Effect of Liquidity, Profitability, Leverage and Activity on Financial Distress - Desta Wijaya, Fitri; Andy Lasmana; Magdalena Melani, Maria (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Financial difficulties are a problem that occurs in company liquidity, difficult to solve if there is no change in the company structure. When financial difficulties occur, companies experience a lack of working capital. Lack of working capital can be caused by high operating costs or liabilities. Companies experiencing financial difficulties will file for bankruptcy, however there are some companies that do not do this, because the company is still able to survive amidst the problems that occur. The aim of the research is to see how liquidity, profitability, leverage and activity influence financial distress in transportation companies listed on the Indonesian stock exchange in 2018-2022. The research method uses a quantitative descriptive research design with SPSS 26 as a data analysis tool. The research population was 46 transportation companies and the sampling technique used purposive sampling as many as 8 transportation companies listed on the Indonesian Stock Exchange. The research results show that liquidity and activity have no effect on financial distress. Profitability has been significant positive effect on financial distress. Leverage has a negative and significant effect on financial distress. Simultaneously, liquidity, profitability, leverage and activity have a positive and significant effect on financial distress.